Eye movements and parafoveal preview of compound words: Does morpheme order matter?. Issue 3 (March 2013) - Angele, Bernhard; Rayner, Keith
Recently, there has been considerable debate about whether readers can identify multiple words in parallel or whether they are limited to a serial mode of word identification, processing one word at a time (see, e.g., Reichle, Liversedge, Pollatsek, & Rayner, 2009). Similar questions can be applied to bimorphemic compound words: Do readers identify all the constituents of a compound word in parallel, and does it matter which of the morphemes is identified first? We asked subjects to read compound words embedded in sentences while monitoring their eye movements. Using the boundary paradigm (Rayner, 1975), we manipulated the preview that subjects received of the compound word before they fixated it. In particular, the morpheme order of the preview was either normal ( cowboy ) or reversed ( boycow ). Additionally, we manipulated the preview availability for each of the morphemes separately. Preview was thus available for the first morpheme only ( cowtxg ), for the second morpheme only ( enzboy ), or for neither of the morphemes ( enztxg ). We report three major findings: First, there was an effect of morpheme order on gaze durations measured on the compound word, indicating that, as expected, readers obtained a greater preview benefit when the preview presented the morphemes in the correct order than when their order was reversed. Second, gaze durations on the compound word were influenced not only by preview availability for the first, but also by that for the second morpheme. Finally, and most importantly, the results show that readers are able to extract some morpheme information even from a reverse order preview. In summary, readers obtain preview benefit from both constituents of a short compound word, even when the preview does not reflect the correct morpheme order.